Protective effect of Growth Hormone-Releasing Hormone agonist in bacterial toxin-induced pulmonary barrier dysfunction - Czikora, Istvan; Sridhar, Supriya; Gorshkov, Boris; Alieva, Irina B.; Kasa, Anita; Gonzales, Joyce; Potapenko, Olena; Umapathy, Nagavedi S.; Pillich, Helena; Rick, Ferenc G.; Block, Norman L.; Verin, Alexander D.; et al. (Frontiers in Physiology, 2014)
Rationale. Antibiotic treatment of patients infected with G- or G+ bacteria promotes release of the toxins lipopolysaccharide (LPS) and pneumolysin (PLY) in their lungs. Growth Hormone-releasing Hormone (GHRH) agonist JI-34 protects human lung microvascular cells (HL-MVEC), expressing splice variant 1 (SV-1) of the receptor, from PLY-induced barrier dysfunction. We investigated whether JI-34 also blunts LPS-induced hyperpermeability. Since GHRH receptor signaling can potentially stimulate both cAMP-dependent barrier-protective pathways as well as barrier-disruptive protein kinase C pathways, we studied their interaction in GHRH agonist-treated HL-MVEC, in the presence of PLY, by means of siRNA-mediated PKA depletion. Methods. Barrier function measurements were done in HL-MVEC monolayers using Electrical Cell substrate Impedance Sensing (ECIS) and VE-cadherin expression by Western blotting. Capillary leak was assessed by Evans Blue dye incorporation. Cytokine generation in broncho-alveolar lavage fluid was measured by multiplex analysis. PKA and PKC-alpha activity were assessed by Western blotting. Results. GHRH agonist JI-34 significantly blunts LPS-induced barrier dysfunction, at least in part by preserving VE-cadherin expression, while not affecting inflammation. In addition to activating PKA, GHRH agonist also increases PKC-alpha activity in PLY-treated HL-MVEC. Treatment with PLY significantly decreases resistance in control siRNA-treated HL-MVEC, but does so even more in PKA-depleted monolayers. Pretreatment with GHRH agonist blunts PLY-induced permeability in control siRNA-treated HL-MVEC, but fails to improve barrier function in PKA-depleted PLY-treated monolayers. Conclusions. GHRH signaling in HL-MVEC protects from both LPS and PLY-mediated endothelial barrier dysfunction and concurrently induces a barrier-protective PKA-mediated and a barrier-disruptive PKC-alpha-induced pathway in the presence of PLY, the former of which dominates the latter.